언리얼 엔진 나이아가라 파티클 시뮬레이션을 이용한 대규모 메타버스 플랫폼 구현 - 정광무(Kwang-Moo Chung); 정일권(Il-Kwon Jeong); 김진술(Jinsul Kim) (디지털콘텐츠학회논문지, 2024)
최근 코로나19의 유행으로 인해 디지털 기술이 빠르게 발전하고 있으며 메타버스와 같이 새롭게 떠오르고 있는 기술 분야의 연구가 활발히 진행되고 있다. 그러나 대규모 공연장 같은 플랫폼을 위한 메타버스 환경 구축을 위한 선행 연구가 존재하지 않고, 특히 대규모 렌더링 연산을 클라이언트 단에서 최적화하는 연구가 부족하다. 본 논문에서는 언리얼 엔진 5(Unreal Engine 5)라는 게임 개발 및 건축, 시뮬레이션 개발 엔진을 이용하여 클라이언트단에서 수만 명 이상의 인파를 안정적으로 시뮬레이션할 수 있는 메타버스 환경을 구축하는 방법을 제안했다. 언리얼 엔진 5에서 제공하는 나이아가라 파티클 시뮬레이션을 통해 메타버스 플랫폼 상의 플레이어들을 구현했으며, LoD 및 버텍스 애니메이션 기법을 이용하여 그래픽 자원을 최적화하였다. 그 결과, 안정적으로 60FPS를 상회하며 수십만 명 이상을 수용할 수 있었다. Due to the COVID-19 pandemic, digital technology is rapidly advancing, and research in emerging fields such as the metaverse is actively underway. However, no prior research examines the development of metaverse environments such as massive performance venues; especially, there is lack of research on optimizing client-side massive rendering. This study proposes a method for building an metaverse environment that can sustain crowds made up of thousands on the client side using Unreal Engine 5, which is an engine for game development, architecture, and simulation. We simulated a crowd of players on the metaverse platform through Niagara particle simulation provided by Unreal Engine 5 and optimized the graphic resources using the level of detail and vertex animation techniques. As a result, we managed to accommodate over 100,000 people while exceeding a frame rate of 60 fps. KCI Citation Count: 0